The mental image of library and information science among Arab newspaper readers: a descriptive analytical study - Sara Mohamed (Cybrarians Journal, 2025)
The daily press plays a vital role in raising awareness among individuals in the community about ongoing local and global events. It also serves as a crucial platform for conveying the opinions and ideas of its members to the largest possible number of interested readers who follow current happenings. The study derives its significance from the importance of journalism in providing information and news to readers, as well as from the significance of library and information science in the creation, collection, organization, provision, retrieval, and utilization of information. This, in turn, enhances scientific research and culture within society. Therefore, the study's importance lies in understanding the information provided by daily newspapers regarding library and information science, as well as in identifying the types of issues that occupy Arab newspapers and the role these publications play in addressing them. This is based on what is published for all members and categories of society across various geographic areas, and it helps in monitoring the public's perception of library and information science among readers. The study aimed to identify the mental image and attitudes formed among readers toward this field. The study employed the descriptive-analytical survey method, using the descriptive approach to explore readers' perceptions of library and information science. Data collection tools included a questionnaire directed at a sample of newspaper readers, which covered four key areas. The study yielded several results, including a finding that 67.4% of the sample expressed interest in library and information science. Additionally, 57.4% held a positive view of the field, while 39.8% sometimes followed library and information issues through the press, whether in print or electronic form. "Al-Youm Al-Sabea" was the most preferred newspaper among the sample members, with 63.9% indicating it as their choice. This newspaper is considered one of the most significant Egyptian private electronic publications. Furthermore, 55.7% of the study sample agreed that journalistic content effectively presents the role played by libraries in society. Additionally, 57.2% recognized the "cultural role" that journalistic content about libraries contributes to society. Finally, 45.0% of the sample appreciated the press's coverage of library and information issues as complementary to what other media outlets offer.